Understanding Key Factors Affecting Online Purchasing Behavior in a Municipality in the Philippines - Melchor, Madonna (Journal of Interdisciplinary Perspectives, 2024)
The study aimed to know the profile of the respondents and the key factors influencing the online purchasing behavior of consumers in the municipality of Bongabong. The researcher employed a descriptive-correlational survey method using a self-made questionnaire. Frequency percentage was used to determine the profile of the respondents in terms of age, gender, status, income or allowance, and frequency of online shopping. Weighted mean was utilized to determine the factors influencing online purchasing behavior, and the Chi-square test of Independence (also known as Pearson's chi-square test) to test the hypothesis of the study performance. The majority of the respondents were students and showed minimal income or allowance. At the same time, they strongly agreed that perceived usefulness, ease of use, and price influenced their online purchasing behavior. The result also indicates significant relationships between the profile of the respondents and the factors influencing online purchasing behavior.